Histomorphochemical studies on cardiac conduction system of prenatal buffalo - GUPTA, ANURADHA; BANSAL, NEELAM; UPPAL, VARINDER (The Indian Journal of Animal Sciences, 2015)
Histomorphological and histochemical studies were conducted on cardiac conduction system of buffalo heart during prenatal development. Foetuses (20) ranging from 13 cm CVRL (87days) to 104 cm CVRL (308 days) were used for study. The heart tissues were fixed in 10% buffered neutral formalin (BNF) and routinely processed. The paraffin sections of 5–7 μm thickness were stained with various stains to study the histomorphological and histochemical details. The study revealed that sinoatrial node was subepicardial and wedged at the junction of anterior vena cava with right atrium in 25 cm CVRL (130 days) foetus. Nodal and Purkinje type specialized cells were observed in sinoatrial node. The atrio-ventricular node was present in the base of atrial septum in front of coronary sinus under the endocardium. The branch of right bundle was first noticed in 13 cm CVRL (87 days) buffalo foetus. The sinoatrial node and right bundle branch showed intense reaction for acid and neutral mucopolysaccharides and basic proteins in all the age. A moderate to strong sudanophilic reaction was found in Purkinje fibers, nodal cells of sinoatrial node and branch of right bundle.